Serial Analysis of Gene Expression: Applications in Malaria Parasite, Yeast, Plant, and Animal Studies - Tuteja, Renu (Hindawi Publishing Corporation, 2004)
The serial analysis of gene expression (SAGE) method is based on the isolation of unique sequence tags from individual transcripts and concatenation of tags serially into long DNA molecules. SAGE is an innovative technique that offers the potential of cataloging both the identity and relative frequencies of mRNA transcripts in a given RNA preparation. It can quantify low-abundance transcripts and reliably detect relatively small differences in transcript abundance between cell populations. SAGE data can be used to complement studies in cases where other gene expression methods may be more convenient or efficient. SAGE can be used in a wide variety of applications to identify disease-related genes, to analyze the effect of drugs on tissues, and to provide insights into the disease pathways. The most important application of SAGE is the identification of differentially expressed genes. In this review, we describe various applications of this powerful technology in malarial parasite, yeast, plant, and animal systems.